Influência de preparos apicais largos e da complementação do preparo químico-mecânico com limas autoajustáveis na redução de endotoxinas em retratamentos endodônticos - Ferreira, Vivian Maia Durange (2016)
The aim of this clinical study was to evaluate the efficacy of large apical preparations and additional instrumentation root canals with SAF system (New redent, Ra'anana, Israel) in removing endotoxin from endodontically treated teeth with apical periodontitis. 10 teeth with a single root and a single channel, endodontically treated, and radiographic evidence of periapical bone destruction and the need for endodontic retreatment were used. Gutta-percha fillings were partially removed using R25 files (Reciproc System VDW), and saline solution was used for irrigation. Then, an initial sample of endotoxin (S1) was collected from the root canal using sterile absorbent paper cones. In the second step, the root canals were repreparados with a new file R25 and irrigated with 2.5% NaOCl, and endotoxin second sample (S2) was collected. The instrumentation of the root canal and irrigation continued using an R40 file (System Reciproc, VDW). Then, the third sample of endotoxin (S3) was collected. The canal preparation was then completed using SAF under continuous irrigation with 2.5% NaOCl, and collecting the fourth sample of endotoxin (S4). The samples of endotoxin (S1, S2, S3 and S4) were diluted and quantitated by turbidimetric method Pyrogent-5000®, utilizing the reaction of Limulus amebocyte lysate (LAL). The results were statistically analyzed by the Kolmogorov-Smirnov, Friedman and Kruskal-Wallis. After removal of the filling material, endotoxin was detected in 100% of the investigated root channel (S1 4.84 EU / ml). After instrumentation with R25 file (S2), there was significant reduction in percentage of 81.20% (0.91 EU / ml, P <0.05). The instrumentation of root canals with R40 file was able to significantly reduce residual endotoxin (S3 0.10 EU / ml, P <0.05). No differences were found between the mean percentages of endotoxin reduction achieved with R40 (S3, 97.93%) and SAF (S4, 96.70%) (P> 0.05). It is concluded that large apical preparations are able to reduce the amount of LPS in the case of endodontically treated teeth presenting apical periodontitis, but the completion of the chemical-mechanical preparation with the SAF system is unable to promote this reduction endotoxin.